Mikroskopija pri Brewstrovem kotu - Čoga, Lucija (Obzornik za matematiko in fiziko, 2015)
We present basic principles of operation of Brewster angle microscopy. We also describe structural organization in thin films of organic molecules floating on water surface. In the last part we give some examples of images of this kind of surface structures obtained by the presented optical microscopy technique.
Keywords: microscopy; mikroskopiranje; tankoplastne strukture; thin surface films; tehnika BAM; enomolekulske plasti